2008
DOI: 10.1128/iai.00875-08
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage 2851 Is a Prototype Phage for Dissemination of the Shiga Toxin Variant Gene 2c in Escherichia coli O157:H7

Abstract: and Stx2, are produced in STEC O157. Variants of the Stx2 type (Stx2, Stx2c) are associated with high virulences of these strains for humans. A bacteriophage designated 2851 from a human STEC O157 encoding the Stx2c variant was described previously. Nucleotide sequence analysis of the phage 2851 genome revealed 75 predicted coding sequences and indicated a mosaic structure typical for lambdoid phages. Analyses of free phages and K-12 phage 2851 lysogens revealed that upon excision from the bacterial chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…It differs from the prototypical Stx2a-encoding phages BP-933W in its chromosomal integration site, phage morphology, and superinfection immunity (43,44). The Stx2c prophage found in lineage I/II strains (i.e., EC4115) have gene content and architecture similar to phage 2851 (23).…”
Section: Discussionmentioning
confidence: 99%
“…It differs from the prototypical Stx2a-encoding phages BP-933W in its chromosomal integration site, phage morphology, and superinfection immunity (43,44). The Stx2c prophage found in lineage I/II strains (i.e., EC4115) have gene content and architecture similar to phage 2851 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, this amplicon was recovered in only one sample of effluent treated by PAA (1/4 or 25%), thus underscoring the possible activity of this disinfectant in reducing the potential health hazard associated with the presence of the stx genes. In fact, the stx1/stx2 genes are widely distributed among E. coli (Shiga-toxin-producing E. coli or verotoxin-producing E. coli) and Shigella strains and among other waterborne bacteria because of their dissemination via bacteriophages [25,26]. However, the presence of stx genes is essential but not sufficient to cause infection because other major virulence factors (e.g., the eae gene) could play an important role [27].…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
“…All experiments were performed with the LightCycler 480 Real-Time PCR System (Roche), using cDNA samples from lysogenic bacteria. Steady-state levels of transcripts of W24 B , 933W and l genes were compared in parallel to the 16S rRNA, according to a procedure described by Strauch et al, (2008), and it was found to be stable. Primers, presented in Table 3, were developed by Primer3web (version 4) and produced by Sigma Aldrich or GENOMED.…”
Section: Methodsmentioning
confidence: 99%